Rain with wind influence on moisture content in buildings protective-decorative outer walls/Lietaus su vėju poveikis pastatų išorinių sienų apsauginės-apdailinės sienutės drėgminiam būviui - Paukštys, Valdas (Journal of Civil Engineering and Management, 2000)
Dry walls in buildings are the main conditions predetermining the durability of a building, the comfort of premises and service life expenses for repair. The probability of rain sorption into external layer of a wall is increased when porous concrete, lightweight bricks and high-insulated structures are applied for walls. Several methods of moisture penetration into building structures could be defined. If a building envelope is characterised by high air permeability, the speed of the wind during rain time has the most important influence on the moisture penetration. When porous materials are used which are known for high capillary water saturation, the duration of rain could be considered as the most important indicator of moisture penetration. With the purpose of estimating the effect of pressure on moisture penetration, small dimension wall fragments of silicate bricks with split surface, samples of concrete-lime mortar and separate samples of them were taken for investigating rain penetration under wind pressure in a special climatic chamber. Materials were selected due to the fact that significant part exterior surfaces in Lithuanian houses are namely of silicate bricks. Silicate bricks with split surfaces absorb moisture well and are suitable as the object of study. In order to study the impact of rain with wind on the moisture content in the walls, a special stand was used (Fig 2). The speed of the wind (m/s) was simulated respectively to pressure (Pa) to facilitate the experiment. The stand was attached to the surfaces of the wall under investigation. Equivalent pressure was formed in the stand during the irrigation. The dependency of the saturation speed upon the rain intensity and formed pressure determined in the entire structure and for separate samples. The results of testing saturated wall fragments have proved that the wall of split silicate bricks with concrete mortar becomes soaked much faster in comparison with considered samples of materials. First, the spots of moisture on the other side of the wall appear over seams. It means that the permeability of structure is usually related to constructional peculiarities of junctions, the quality of mounting and, less often, to certain peculiarities of the material itself. Water together with infiltrated airflow is moving through voids, chink and leaky points in seams. The higher the speed of wind, the higher the pressure on surface of a wall, which predetermines the volume of infiltrated air. Consequently, when the volume of infiltrated air increases, the probability that the wall shall become soaked faster also increases.Article in Lithuanian.First Published Online: 26 Jul 2012